Thomas Aquinas on Virtue: Directions for Future Inquiry - Osborne, Thomas M. (The Thomist, 2024)
This article is a reflection in response to reviews of my book, Thomas Aquinas on Virtue. I suggest that Thomas's philosophy, especially as contained in the Summa theologiae, is simply the part of natural knowledge, scientific in the Aristotelian sense, that is needed for theology, and that this natural knowledge might be supplemented with what we have learned from the contemporary sciences. Moreover, new editions of historically significant texts allow us to better understand Thomas's philosophical and theological achievements. Finally, Thomas's account of virtue could be enriched through responding to problems raised in our contemporary cultural context and incorporating aspects of non-Western traditions of philosophical enquiry, such as Confucianism.